Distinguishing between long-range dependence and deterministic trends - Philipp Sibbertsen; Ioannis Venetis (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2003)
We provide a method for distinguishing long-range dependence from deterministic trends such as structural breaks. The method is based on the comparison of standard log-periodogram regression estimation of the memory parameter with its tapered counterpart. The difference of these estimators provides the desired test. Its asymptotic distribution depends on the true memory parameter under the null, and is therefore estimated by bootstrapping. The test is applied to inflation rates of three industrialized countries.
Keywords: C12; C22; C14; 519; Long memory; trends; log-periodogram regression; inflation rates; Zeitreihenanalyse; Schätztheorie; Inflationsrate; Schätzung; USA; Großbritannien; Deutschland